Hydrazide–Hydrazones as Potential Antitubercular Agents: An Overview of the Literature (1999–2023) - Mali, Suraj N.; Pandey, Anima; Shah, Umang; Jawarkar, Rahul D; Somani, Rakesh (SynOpen, 2024)
Hydrazide–hydrazone derivatives are prevalent in numerous bioactive compounds, showcasing a diverse array of biological effects including antibacterial, antitubercular, antifungal, anticancer, anti-inflammatory, anticonvulsant, antiviral, and antiprotozoal properties. Consequently, numerous medicinal chemists have undertaken the synthesis of various hydrazide–hydrazones, subjecting them to evaluation for their biological activities. Among these, antituberculosis activity stands out as a recurring focus in the scientific literature. This paper provides a comprehensive overview of research spanning the last 24 years (1999–2023), concentrating on the antituberculosis properties of hydrazide–hydrazone derivatives. The insights presented herein could serve as a valuable roadmap for the development of novel hydrazide–hydrazones with potential antimicrobial efficacy.
Keywords: hydrazide–hydrazone; antituberculosis; recent advances; tuberculosis